Simulation of denitrification and ozone loss for the Arctic winter 2002/2003 - Grooss, J.-U.; Günther, G.; Müller, R.; Konopka, P.; Bausch, S.; Schlager, H.; Voigt, C.; Volk, C.M.; Toon, G. C. (CCSD, 2005)
International audience We present simulations with the Chemical Lagrangian Model of the Stratosphere (CLaMS) for the Arctic winter 2002/2003. We integrated a Lagrangian denitrification scheme into the three-dimensional version of CLaMS that calculates the growth and sedimentation of nitric acid trihydrate (NAT) particles along individual particle trajectories. From those, we derive the HNO 3 downward flux resulting from different particle nucleation assumptions. The simulation results show a clear vertical redistribution of total inorganic nitrogen ( ), with a maximum vortex average permanent removal of over 5ppb in late December between 500 and 550K and a corresponding increase of of over 2ppb below about 450K. The simulated vertical redistribution of is compared with balloon observations by MkIV and in-situ observations from the high altitude aircraft Geophysica. Assuming a globally uniform NAT particle nucleation rate of 7.8x10 -6 cm -3 h -1 in the model, the observed denitrification is well reproduced. In the investigated winter 2002/2003, the denitrification has only moderate impact (?14%) on the simulated vortex average ozone loss of about 1.1ppm near the 460K level. At higher altitudes, above 600K potential temperature, the simulations show significant ozone depletion through -catalytic cycles due to the unusual early exposure of vortex air to sunlight.